Single point mutation detection in living cancer cells by far-red emitting PNA–FIT probes. Issue 11 (6th January 2016) - Kolevzon, N.; Hashoul, D.; Naik, S.; Rubinstein, A.; Yavin, E.
Abstract : SNP detection of the mutated kRAS oncogene in living cells is shown to be achieved for the first time by cell-permeable and far-red emitting PNA–FIT probes. Abstract : Peptide nucleic acid bis-quinoline conjugates are reported as attractive far-red emitting probes that detect mutated mRNA in living cells at SNP resolution.